Semantic Outbreak Power Based Evolution of Web Event in Large-Scale Ubiquitous Contexts. (7th July 2015) - Xu, Zheng; Chen, Hai-Yan
Abstract : Nowadays, emergencies' events have a great impact on people's daily life. Web is acting as an important platform for the diffusion and evolution of social events. With the popularization and development of web technology in the world, web is becoming an important platform to cover, transmit, and release the news. Information holders can use Internet as a medium to broadcast various news in real time. But it is difficult for people to excavate the events development trend from web information. In this paper, we introduce a method to measure the evolution process of the Web event based on the semantic outbreak power. Then, we propose an approach to distinguish the event type based on the fuzzy recognition. Finally, we give some instances validation of semantic outbreak power of web event and the correctness verification of the event type distinguish of Web event.